Intergenerational Mobility of Immigrants by Refugee Status: An Analysis of Linked Landing Files and Tax Records - Wifag Adnan; Jonathan Zhang; Angela Zheng (Institute of Labor Economics (IZA), 2023)
A large literature shows that the children of immigrants have high upward mobility. However, immigrants vary vastly in how they are selected: while economic immigrants are chosen based on skill and education, refugees migrate at times of conflict and war. In this paper, we study the mobility of immigrants by admission class. Using administrative data linking the universe of immigrant landing documents with tax records in Canada, we estimate intergenerational mobility outcomes by refugee status. We find that for immigrant parents at the 25th percentile of the income distribution, refugee children have an expected rank of 47 percentiles, while the corresponding estimate for non-refugee children is 51 percentiles. Approximately 60% of this gap can be explained by differences in parental attributes upon arrival, indicating that selection contributes to higher mobility. Finally, we show that when correcting for the underplacement of immigrant parents, the absolute upward mobility of refugees at p25 is largely unaffected while that of non-refugees falls by around 2 percentiles.
Keywords: J61; J62; J15; 330; intergenerational mobility; refugees; immigration